Variación longitudinal de los elementos del leño en Schinopsis quebracho-colorado (Schlecht.) Barkl. et Meyer Anacardiaceae - Giménez, Ana María; López, Carlos Raúl (Instituto de Ecología, A.C., 2016)
The aim of the study is to determine longitudinal gradient of variation of wood elements of Schinopsis quebracho-colorado (Schlecht.) Barkl. et Meyer, Anacardiaceae. The study was carried out in ten individuals from Los Pirpintos, Copo Department, Santiago del Estero, Argentina. Healthy, well formed trees, with more than 30 cm DBH (diameter to the breast height, 1,30 m) were selected  from dominant canopy. Wood samples were taken following the methodology of Helinska et al. (1991) and terminology of IAWA (IAWA, 1989). Anatomical variable selects are: rings width, vessel number/mm2, vessel tangential diameter, vessels and rays length, proportion of tissues, percentual type pore, external and internal diameter and fiber wall thickness. This wood presents a longitudinal gradient from base to apex. The characteristics that determine wood variability are: fibers length, number of pores/mm2, and fibers wall thickness. Fiber length and number of pores/mm2 decrese from base to apex. Fiber wall thickness increases from base to apex.The principal source of variability is between trees. Wood is heterogeneus. More investigations about heigt gradient are necessary.